COXSACKIEVIRUS B5 ASSOCIATED WITH MYOCARDITIS CASE - Russo, DH; Luchs, A; Machado, BC; Carmona, RCC; Timenetsky, MCST (Revista do Instituto Adolfo Lutz, 2009)
Myocarditis is an inflammatory disease of the cardiac muscle caused by myocardial infiltration of immunocompetent cells following any kind of cardiac injury. Enterovirus are common pathogens which cause a broad spectrum of illnesses, including acute myocarditis, in fact, the six serotypes of the group B coxsackieviruses are common human enteroviruses linked etiologically to inflammatory cardiomyopathies. Biological samples, stool and paired sera, from a child who presented acute myocarditis were sent to the Enteric Virus Laboratory of the Adolfo Lutz Institute for laboratory diagnosis to be performed. A viral sample isolated in RD (human rhabdomyosarcoma cells) was subjected to the polymerase chain reaction and showed a 437-base pair product that was characteristic of the Enterovirus genus. Coxsackievirus B5 (CB5) serotype was identified using the indirect immunofluorescence test. In addition, paired serum samples presented seroconversion to CB5. Besides CB5 consistently appeared among the most commonly serotype associated to myocarditis, it seems to be rare in Brazilian pediatric population. Additional studies are important to investigate the Enteroviruses association with myocarditis in our area.